Glorund, a Drosophila hnRNP F/H homolog, is an ovarian repressor of nanos translation. - Kalifa, Y.; Huang, T.; Rosen, L.N.; Chatterjee, S.; Gavis, E.R. (Developmental Cell, 2006)
Patterning of the anterior-posterior body axis of the Drosophila embryo requires production of Nanos protein selectively in the posterior. Spatially restricted Nanos synthesis is accomplished by translational repression of unlocalized nanos mRNA together with translational activation of posteriorly localized nanos. Repression of unlocalized nanos mRNA is mediated by a bipartite translational control element (TCE) in its 3' untranslated region. TCE stem-loop II functions during embryogenesis, through its interaction with the Smaug repressor. Stem-loop III represses unlocalized nanos mRNA during oogenesis, but trans-acting factors that carry out this function have remained elusive. Here we identify a Drosophila hnRNP, Glorund, that interacts specifically with stem-loop III. We establish that the ability of the TCE to repress translation in vivo reflects its ability to bind Glorund in vitro. These data, together with the analysis of a glorund null mutant, reveal a specific role for an hnRNP in repression of nanos translation during oogenesis.